SAMPAH: BANJIR, PENYAKIT, DAN NILAI EKONOMI - Hasanuddin; Mugiarso; Pratiwi Nila Sari; Tutiek Yoganingsih (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
Bekasi Regency is experiencing serious problems regarding waste management. Waste production reaches 2,100 tons and only 800 tons can be transported to the final disposal site (TPA) Burangkeng, meaning that 1,300 tons of waste remains in the temporary disposal site (TPS). One of the reasons is the lack of waste fleet owned by the Bekasi Regency government, currently there are around 112 units available, while what is needed is around 320 units. With the accumulation of garbage, of course, it has negative impacts, such as floods, disease, and gives the environment a slum impression. Public awareness must be built so that they can take part by not littering. For this reason, community service activities are carried out to convey the various dangers that can arise from waste. It was also conveyed that waste if handled properly will provide economic value for families and communities. This community service activity is carried out by means of lectures and direct dialogue with the community, and jointly formulating a program on how to change waste so that it has economic value. Keywords : Garbage, flood, disease, economic value.